IMPACT OF STRENGTHENING BUSINESS ETHOS ON AGRARIAN RESOURCE-BASED MICRO ENTERPRISES - Aristiono Nugroho (Jurnal Impresi Indonesia, 2024)
Even though it is located in a karst area, the community and Pucung Village Government are optimistic that they will be able to advance their area into an independent, peaceful, and prosperous village. For this reason, they are trying to ensure that micro-businesses in this village contribute to its progress by strengthening their business ethos. This phenomenon is interesting to research using qualitative research methods accompanied by a rationalistic approach. The number of informants was 15 people, selected purposively. Data consists of (1) Primary data obtained from interviews with informants and (2) Secondary data in the form of population data for Pucung Village. Meanwhile, data analysis was carried out using Qualitative Analysis Techniques. The research results show that their business ethos determines the long-term success of micro-businesses, so strengthening their business ethos needs to be done. Pucung Village has 6 (six) types of micro-businesses, consisting of 8 (eight) business units located in 8 (eight) locations. Strengthening the business ethos for micro businesses in Pucung Village has elements, including the business owner's willingness to set a vision and mission, build a positive business culture, and commit to quality. When strengthening the business ethos has been carried out, it will have an impact in the form of increasing productivity, competitiveness, credibility, and the ability to survive.